2023
DOI: 10.3390/diagnostics13050936
|View full text |Cite
|
Sign up to set email alerts
|

Precision Medicine for Chronic Endometritis: Computer-Aided Diagnosis Using Deep Learning Model

Abstract: Chronic endometritis (CE) is a localized mucosal infectious and inflammatory disorder marked by infiltration of CD138(+) endometrial stromal plasmacytes (ESPC). CE is drawing interest in the field of reproductive medicine because of its association with female infertility of unknown etiology, endometriosis, repeated implantation failure, recurrent pregnancy loss, and multiple maternal/newborn complications. The diagnosis of CE has long relied on somewhat painful endometrial biopsy and histopathologic examinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Several major factors are currently considered responsible for reproductive dysfunction in CE [20]: this is primarily the abnormal uterine microbiome, as demonstrated by a suffi cient number of microbiological studies [1,[47][48][49][50], the disruption of cytobiochemical and immune processes in the endometrium [28,36,[51][52][53][54], and also confi rmed by the improved fertility following antibacterial therapy in CE patients [34,55,56]. The abnormal uterine microbiome leads to immune deviations primarily affecting the leukocyte pool of immunocompetent cells with a change in the ratio of pro-and anti-infl ammatory cytokines, which results in the reduced implantation capacity of the endometrium and prevents embryo invasion [19,20,22,57].…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several major factors are currently considered responsible for reproductive dysfunction in CE [20]: this is primarily the abnormal uterine microbiome, as demonstrated by a suffi cient number of microbiological studies [1,[47][48][49][50], the disruption of cytobiochemical and immune processes in the endometrium [28,36,[51][52][53][54], and also confi rmed by the improved fertility following antibacterial therapy in CE patients [34,55,56]. The abnormal uterine microbiome leads to immune deviations primarily affecting the leukocyte pool of immunocompetent cells with a change in the ratio of pro-and anti-infl ammatory cytokines, which results in the reduced implantation capacity of the endometrium and prevents embryo invasion [19,20,22,57].…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
“…Hysteroscopy has suffi cient sensitivity; however, it is highly dependent on the technician [33][34][35]. Therefore, the current gold standard for CE diagnosis is the detection of plasma cells (PCs) in endometrial biopsy material [36][37][38]. The number of PCs required to diagnose CE remains a matter of discussion [38,39].…”
Section: Introductionmentioning
confidence: 99%
“…Fluid hysteroscopy has been recently proposed as a versatile and convenient diagnostic tool that can be utilized in gynecologic practice to detect uterine cavity lesions associated with female infertility, such as endometrial polyps, submucosal leiomyomas, intrauterine adhesions, and uterine septum [ 31 ]. Recent studies have also demonstrated the potential utility of fluid hysteroscopy for the endoscopic diagnosis of chronic endometritis (CE) since it represents a less painful and time-consuming alternative to traditional endometrial biopsy [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the retrospective study by Cicinelli et al showed that endometrial micropolyposis can easily be detected by fluid hysteroscopy; moreover, histopathologic evidence of plasma cells was less frequently identified in women without hysteroscopic evidence of micropolyposis [ 34 ]. In another retrospective study, the positive and negative predictive values of fluid hysteroscopy detecting the triad of endometrial micropolyposis, stromal edema, and focal/diffuse hyperemia for the presence of histopathologic CE were 98.4% and 94.5%, respectively [ 32 ]. Based on these studies, the detection of endometrial micropolyposis using fluid hysteroscopy may represent a potentially useful diagnostic tool for CE in infertile women.…”
Section: Discussionmentioning
confidence: 99%
“…In 2022, we launched the ARCHIPELAGO (ARChival Hysteroscopic Image-based Prediction for histopathologic chronic Endometritis in infertile women using deep LeArninG mOdel) study. The goal of this study is to link the findings of HistoCE with those of HysteroCE using deep learning-based CNN models and establish computer-aided detection/diagnosis systems for the biopsy-free, less invasive, accurate/precise diagnosis of this inflammatory disease that can deteriorate endometrial receptivity [ 65 ]. These approaches could potentially benefit infertile women suffering from CE as well as aid us in establishing diagnostic criteria/clinical guidelines for this yet elusive disease.…”
Section: Introductionmentioning
confidence: 99%